Boron nitride-mediated semiconductor nanonetwork for an ultralow-power fibrous synaptic transistor and C-reactive protein sensing. Issue 15 (5th April 2023) - Li, Mufang; Shu, Qing; Qing, Xing; Wu, Jianmei; Xiao, Qing; Jia, Kangyu; Wang, Xungai; Wang, Dong
Abstract : A fibrous OECT constructed by a functional boron nitride-mediated polypyrrole neurofiber and ion-gel dielectric was proposed. Representative synaptic plasticities were mimicked. The synaptic FOECT showed a low power consumption and a good linear monitoring region toward CRP. Abstract : A bioinspired organic electrochemical transistor (OECT) with synaptic and sensing functions has shown great potential in wearable neuromorphic electronics and brain-like sensory systems. Despite the extraordinary progress in simulating neuromorphic functions, it is still difficult to design a synaptic OECT with a bionic structure, long-term durability, low energy consumption and biomarker monitoring capability. Here, a fibrous OECT (FOECT) constructed from functional boron nitride (FBN)-mediated polypyrrole (PPy) neurofibers and an ion-gel dielectric is proposed for the first time. Benefiting from the porous and consecutive PPy nanonetwork, the synaptic FOECT shows a large on–off current ratio (1.46 × 10 4 ) and high transconductance (24.6 mS). Key synaptic features, such as excitatory/inhibitory postsynaptic current (EPSC/IPSC), paired-pulse facilitation/depression (PPF/PPD), short-term plasticity (STP) and cyclic endurance (4000 cycles) were successfully emulated. A low power consumption of 0.85 pj per spike was attained due to the short energy dissipation pathway of the nanostructured PPy channel. In addition, a high surface area and big transconductance guaranteed the FOECT a linear detection region (coefficient R 2 = 0.966) towards 10 pg mL −1 –0.2 mg mL −1 of C-reactive protein (CRP) with good reproducibility. Hence, this work details a promising strategy for next-generation smart textiles with energy-efficient neuromorphic computing and high-performance synaptic devices.